VD_FINDINFO HC / 2014 / 534 vom 5. Mai 2014 - VD Tribunal cantonal (2014)
DIVORCE SUR DEMANDE UNILATÉRALE, OBLIGATION D'ENTRETIEN, ENFANT, REVENU HYPOTHÉTIQUE | 133 al. 1 CC, 285 al. 1 CC, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)